2018
DOI: 10.1172/jci120358
|View full text |Cite
|
Sign up to set email alerts
|

CXCL11-dependent induction of FOXP3-negative regulatory T cells suppresses autoimmune encephalomyelitis

Abstract: The Editors recently posted an Expression of Concern for this article due to duplication of some of the flow cytometry plots in Figures 5C and 7A (1). The authors have completed three replicate experiments for the panels in question, and the updated findings appear below. The revised experiments were conducted by Yaniv Zohar, and the analysis was completed independently in a blinded fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 0 publications
0
44
2
Order By: Relevance
“…Our findings suggested that CXCR3-CXCL10 axis influence MPE formation was linked to the increased recruitment of T H 1 and T H 17 cells into MPE. Aside from chemoattraction, previous studies have shown that CXCR3-CXCL10 interaction drive T H 1 differentiation directly [47]. Reviewing our results, we found the concentration of CXCL10 was decreased in the MPE of WT mice, while the concentration of VEGF was increased, and the tumor vessels were robust in WT mice than IL-10 -/mice with MPE, this suggested that CXCL10 may interfere tumor angiogenesis and it has been demonstrated that CXCL10 inhibits nonsmall cell lung cancer tumorigenesis [48].…”
Section: Cells Interacted With the T H 17 Cells In Mpementioning
confidence: 99%
“…Our findings suggested that CXCR3-CXCL10 axis influence MPE formation was linked to the increased recruitment of T H 1 and T H 17 cells into MPE. Aside from chemoattraction, previous studies have shown that CXCR3-CXCL10 interaction drive T H 1 differentiation directly [47]. Reviewing our results, we found the concentration of CXCL10 was decreased in the MPE of WT mice, while the concentration of VEGF was increased, and the tumor vessels were robust in WT mice than IL-10 -/mice with MPE, this suggested that CXCL10 may interfere tumor angiogenesis and it has been demonstrated that CXCL10 inhibits nonsmall cell lung cancer tumorigenesis [48].…”
Section: Cells Interacted With the T H 17 Cells In Mpementioning
confidence: 99%
“…Zohar et al (2018) Mouse model ↑After CXCL11-Ig ↑After CXCL11-Ig CXCL11 redirects the polarization of effector T cells into Tr1 cells and suppresses EAE in an IL-10 dependent manner.Ni Choileain et al (2017); Ni Choileain & Astier (2011) Human blood ↓ ↓ Altered molecular mass and expression of CD46 are observed in T cells from patients with MS, thus inhibiting the secretion of IL-10 by Tr1 cells. Pennati et al (2016) Mouse model ↑After Breg cell stimulation ↑After Breg cell stimulation Breg cells can improve MS by stimulating Tr1 cell expansion.…”
mentioning
confidence: 99%
“…Real-time PCR was run using the CFX connect TM Real-Time System with the following Primetime primers CXCL9 (assay ID: Mm.PT.58.13098261), CXCL10 (assay ID: Mm.PT.58.43575827), and CXCL11 (assay ID: Mm.PT.58.42838989) (Integrated DNA Technologies; Coralville, IA). We did not measure CXCL11 in the WT samples because c57bl/6 mice have a neutralizing mutation in the CXCL11 gene (Groom and Luster 2011;Sierro et al 2007;Zohar et al 2014); thus, CXCL11 mRNA in these animals would be irrelevant because it fails to encode an effectual protein. Because CXCL10 KO mice were developed with the use of J1 embryonic stem cells (which harbor an intact cxcl11 gene), the KO animals have an intact cxcl11 gene (Dufour et al 2002;Groom and Luster 2011).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…CXCL10 has been implicated in pathological muscle conditions such as inflammatory myopathies (Crescioli et al 2012), but to our knowledge there has been no investigation into the role of CXCL10 in the context of muscle damage and repair in otherwise healthy muscle. CXCL10 binds to the G-protein-coupled receptor CXCR3 to elicit various responses including the directed migration of T cells (Dufour et al 2002;Hoerning et al 2011;Taub et al 1993), T-cell adhesion to endothelial cells (Taub et al 1993), and T-cell effector polarization (Zohar et al 2014). As with most chemokine/receptor axes, additional ligands (CXCL9 and CXCL11) can also engage CXCR3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation